The Vaginal Microenvironment: The Physiologic Role of Lactobacilli - Amabebe, Emmanuel; Anumba, Dilly O. C. (Frontiers in Medicine, 2018)
In addition to being a passage for sperm, menstruum, and the baby, the human vagina and its microbiota can influence conception, pregnancy, the mode and timing of delivery, and the risk of acquiring sexually transmitted infections. The physiological status of the vaginal milieu is important for the wellbeing of the host as well as for successful reproduction. High oestrogen states, as seen during puberty and pregnancy, promote the preservation of a homeostatic (eubiotic) vaginal microenvironment by stimulating the maturation and proliferation of vaginal epithelial cells and the accumulation of glycogen. A glycogen-rich vaginal milieu is a haven for the proliferation of Lactobacilli facilitated by the production of lactic acid and decreased pH. Lactobacilli and their antimicrobial and anti-inflammatory products along with components of the epithelial mucosal barrier provide an effective first line defense against invading pathogens including bacterial vaginosis, aerobic vaginitis-associated bacteria, viruses, fungi and protozoa. An optimal host-microbial interaction is required for the maintenance of eubiosis and vaginal health. This review explores the composition, function and adaptive mechanisms of the vaginal microbiome in health and those disease states in which there is a breach in the host-microbial relationship. The potential impact of vaginal dysbiosis on reproduction is also outlined.